Clinical and Patient-Reported Outcomes From Patients With Nonalcoholic Fatty Liver Disease Across the World: Data From the Global Non-Alcoholic Steatohepatitis (NASH)/ Non-Alcoholic Fatty Liver Disease (NAFLD) Registry - YILMAZ, YUSUF (My University, 2021)
BACKGROUND & AIMS: Globally, nonalcoholic fatty liver disease (NAFLD) is a common cause of chronic liver disease. We assessed the clinical presentation and patient-reported outcomes (PROs) among NAFLD patients from different countries. METHODS: Clinical, laboratory, and PRO data (Chronic Liver Disease Questionnaire-nonalcoholic steatohepatitis [NASH], Functional Assessment of Chronic Illness Therapy-Fatigue, and the Work Productivity and Activity Index) were collected from NAFLD patients seen in real-world practices and enrolled in the Global NAFLD/NASH Registry encompassing 18 countries in 6 global burden of disease super-regions. RESULTS: Across the global burden of disease super-regions, NAFLD patients (n = 5691) were oldest in Latin America and Eastern Europe and youngest in South Asia. Most men were enrolled at the Southeast and South Asia sites. Latin America and South Asia had the highest employment rates (>60%). Rates of cirrhosis varied (12%-21%), and were highest in North Africa/Middle East and Eastern Europe. Rates of metabolic syndrome components varied: 20% to 25% in South Asia and 60% to 80% in Eastern Europe. Chronic Liver Disease Questionnaire-NASH and Functional Assessment of Chronic Illness Therapy-Fatigue PRO scores were lower in NAFLD patients than general population norms (all P < .001). Across the super-regions, the lowest PRO scores were seen in Eastern Europe and North Africa/Middle East. In multivariate analysis adjusted for enrollment region, independent predictors of lower PRO scores included younger age, women, and nonhepatic comorbidities including fatigue (P < .01). Patients whose fatigue scores improved over time experienced a substantial PRO improvement. Nearly 8% of Global NAFLD/NASH Registry patients had a lean body mass index, with fewer metabolic syndrome components, fewer comorbidities, less cirrhosis, and significantly better PRO scores (P < .01). CONCLUSIONS: NAFLD patients seen in real-world practices in different countries experience a high comorbidity burden and impaired quality of life. Future research using global data will enable more precise management and treatment strategies for these patients.
Keywords: Metabolic Syndrome; Outcomes; Chronic Diseases; Disease Burden; Work Productivity